2014
DOI: 10.1159/000366138
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microvascular Invasion and Tumor Necrosis on the Prognosis of Korean Patients with pT1b Renal Cell Carcinoma

Abstract: Objectives: To evaluate prognostic factors in pT1b renal cell carcinoma (RCC) patients for which no specific studies have been conducted on. Methods: The data of 270 patients diagnosed with pT1bN0M0 RCC at 2 institutions between January 1998 and June 2010 were retrospectively analyzed. Univariate and multivariate analyses using Cox proportional hazard models were used to identify pathologic and clinical factors that influenced prognosis. Five-year recurrence-free survival and cancer-specific survival were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Microvascular invasion and microvascular density have been shown to have a significant impact on metastasis, recurrence risk, and survival (21). In the study of Kwon et al, MVI and tumor necrosis in pT1b RCC were found to be independent prognostic factors from tumor stage (22). Bedke et al study showed that MVI was found to be a weak prognostic factor correlating with tumor stage, Fuhrman nuclear grade and sarcomatoid differentiation in RCC (23).…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular invasion and microvascular density have been shown to have a significant impact on metastasis, recurrence risk, and survival (21). In the study of Kwon et al, MVI and tumor necrosis in pT1b RCC were found to be independent prognostic factors from tumor stage (22). Bedke et al study showed that MVI was found to be a weak prognostic factor correlating with tumor stage, Fuhrman nuclear grade and sarcomatoid differentiation in RCC (23).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent probability assessment study showed that tumor aggressiveness exhibited proportional increases of 18%, 24%, and 29% in the likelihood of aggressive histology for 2, 3, and 4 cm RCCs (27). A different study suggested that routine follow-up periods for earlier detection of metastasis or recurrence until 12 years would enable timely interventive treatment to improve survival outcomes, particularly in cases of small tumor burden (28). Patients lost to follow-up reported poor prognostic outcomes (29) and greater tumor burdens, and more progressive metastatic states showed higher tumor heterogeneity in RCC (16).…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, RN is the preferred treatment strategy. Furthermore, multiple researchers have shown that MVI is an important factor in the prognosis of RCC (4)(5)(6). The diagnosis of MVI mainly based on histopathological analysis.…”
Section: Introductionmentioning
confidence: 99%